1996
DOI: 10.1002/eji.1830261026
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of recombinant chicken interferon‐γ

Abstract: Supernatants of the chicken T cell line 855 contain antiviral and macrophage activating factor activity and strongly activate transcription of the guanylate binding protein (GBP) gene in chicken cells. To characterize the cytokine responsible for the GBP-inducing activity, we chose a cDNA expression cloning strategy in COS cells. Sequencing a positive clone revealed that it encode chicken interferon-gamma (ChIFN-gamma). Histidine-tagged ChIFN-gamma was expressed in Escherichia coli and purified by nickel chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 38 publications
1
74
0
Order By: Relevance
“…RNA samples were size fractionated by electrophoresis through agarose gels containing 4% formaldehyde using standard procedures before blotting onto nylon membranes and hybridization with the indicated cDNA probes that were radiolabeled with 32 Purification of Histidine-tagged Recombinant Proteins from Escherichia coli-Purification of histidine-tagged chIFN-␥ and MxA by affinity chromatography on nickel chelate agarose was described previously (45,46).…”
Section: Methodsmentioning
confidence: 99%
“…RNA samples were size fractionated by electrophoresis through agarose gels containing 4% formaldehyde using standard procedures before blotting onto nylon membranes and hybridization with the indicated cDNA probes that were radiolabeled with 32 Purification of Histidine-tagged Recombinant Proteins from Escherichia coli-Purification of histidine-tagged chIFN-␥ and MxA by affinity chromatography on nickel chelate agarose was described previously (45,46).…”
Section: Methodsmentioning
confidence: 99%
“…COS-7 cells were grown in DMEM supplemented with 10% fetal calf serum. Primary macrophages were prepared from chicken blood and cultured as described [28].…”
Section: Methodsmentioning
confidence: 99%
“…His-ChIL-1β was purified by affinity chromatography on a nickel chelate agarose column. Purification conditions were exactly as described for chicken interferon-γ [28]. Peak column fractions were pooled and samples were frozen at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
“…3). IFN-γ has been demonstrated to possess potent stimulatory effects on cell-mediated immunity in chickens [24]. Protection of newly hatched chickens against infection by invasive salmonellae has been associated with enhanced cell-mediated indices of immunity [6].…”
Section: Discussionmentioning
confidence: 99%
“…Since the gene coding a chicken IFN-γ (ChIFN-γ) was isolated and sequenced by Digby and Lowenthal [3], many reports have been published to produce recombinant ChIFN-γs [3,8,20,21,24]. Lowenthal et al [11] showed enhancement of antibody responses in chickens co-administered of ChIFN-γ with sheep red blood cells.…”
mentioning
confidence: 99%